1978
DOI: 10.5271/sjweh.2710
|View full text |Cite
|
Sign up to set email alerts
|

Relation between radiological pleuropulmonary changes, clinical history and weight index of construction workers.

Abstract: 4 (1978) 179-183. Photofluorography was performed on 1,542 male construction workers in the Stockholm area. Postero-anterior, lateral and two anterior oblique views were obtained. The pleural and pulmonary changes found were classif~ed into six groups. The results were correlated to the subjects' calculated weight index and to the occupational history of asbestos exposure and previous lung or pleural disease. There was a strong positive assoc1ation between a high weight index and changes interpreted as increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The ILO Classification 2000 version defined the minimum width to be 3 mm or more, the same as the JNR modification. In addition, there are several plaque definitions by Scandinavian specialists 19,36,37,[41][42][43] , all of which defined only bilateral pleural thickening as pleural plaques, excluding unilateral ones. Therefore, to evaluate the frequencies of pleural plaques, studies should describe the criteria being used.…”
Section: Diagnostic Criteria On Plain Radiographsmentioning
confidence: 99%
“…The ILO Classification 2000 version defined the minimum width to be 3 mm or more, the same as the JNR modification. In addition, there are several plaque definitions by Scandinavian specialists 19,36,37,[41][42][43] , all of which defined only bilateral pleural thickening as pleural plaques, excluding unilateral ones. Therefore, to evaluate the frequencies of pleural plaques, studies should describe the criteria being used.…”
Section: Diagnostic Criteria On Plain Radiographsmentioning
confidence: 99%
“…In an earlier investigation of Swedish construction workers II % had pleural plaques (13), and an investigation with thoracoscopy showed that 67% of construction workers have pleural plaques when more than 30 years have elapsed since their first employment (14). In this investigation 24% of the individuals had pleural plaques or diffuse pleural thickening.…”
Section: Discussionmentioning
confidence: 99%